(untitled) - Mesnooh, Christopher Joseph (Dordrecht, Netherlands, 1994)
World-wide clientele. It sets forth in clear, non-technical language, the full range of legal considerations which foreign investors will need to consider in order to successfully carry out their activities in France. Although the primary focus of this work is French law, Community law is also treated whenever necessary so as to provide the reader with the fullest possible framework. This volume explains company formation, sales and distribution methods, corporate and personal income taxation, investment regulations, mergers and acquisitions, corporate restructurings, liquidation, antitrust regulation, intellectual property, the banking and environmental regulatory framework and labor and immigration law. It also contains an invaluable French--English legal glossary designed to assist the reader in understanding contracts and legal correspondence exchange during commercial transactions of any nature. Due to the balance struck between a thorough treatment of legal considerations and the desire to avoid overly technical language, this volume is appropriate to attorneys, business people and all investors wishing to acquire a well-informed view concerning the legal regulation of commerce in France. Its concise format permits rapid consultation and thus allows its reader to efficiently obtain the information needed to successfully structure and complete commercial transactions in France
Keywords: Business enterprises, Foreign,Investments, Foreign,Taxation,Trade regulation; Law and legislation,Law and legislation; France,France,France,France